Banjar Siam Orange Ice Cream: A Catalyst for Village Tourism - Arif Sholahuddin; Rusmansyah; Mahdian; Leny; Syahmani; Anisa; Aliman; Handi Al Fakhri; Muhammad Ismi Rezani (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
The main challenge faced by the Karang Bunga Village community is the low price of Siam Banjar oranges during the harvest season, which negatively affects the farmers' economy. To address this issue, it is necessary to diversify processed citrus products as part of the Citrus House business unit managed by the Village-Owned Enterprise (BUMDes)